(3eaGNQ GdHQHQs
(3ChdgG (B:s
(3GdMeO ddg QH GdYGdejf CeG HYO aEfg deG cGfJ GdHQHQ YfO cKjQ ef LgdI GdfGS CNS GdCee s
(3BNQgG (B:s
(3acGf GdbJdi hGdZQbi efge CQHYI BdGa aGQS GfJgi eG dNU ef gPg GdbUI s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH GdKGfis
(3hQO GdcJGH ai cJGH CfSGH GdeZQH dCHi MjGf HQbe (B45 (3ef HYKI GdeZQH GdChdi ef GdNRGfI GdYGeIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B7 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B255s
(3eUOQ GbJfGA GdCUd (B:s
(3ef GdNRGfI GdYGeI HeOjfI GdQHGW (B(1275(3c(B) s
Keywords: (3GdCOHs